Ultrasound sonication prior to electrospinning tailors silk fibroin/PEO membranes for periodontal regeneration - Serôdio, Ricardo (2019)
In this study, silk fibroin (SF)/poly(ethylene oxide) (PEO) membranes were designed and fabricated by combining ultrasound sonication prior to electrospinning (0 to 20 min) as a strategy to physically control the rheological properties of solutions (10 to 30% w/v PEO) and to improve the spinnability of the system. PEO has proved to be essential as a co-spinning agent to assure good membrane reproducibility and enough flexibility for clinical manipulation. The rheological tests indicated that sonication greatly increased the viscosity of SF/PEO solutions and further enhanced the quality of the produced electrospun fibers with consequent improved mechanical properties in dry and wet conditions. By tuning the viscosity of the solutions using a simple sonication step prior to electrospinning, it was possible to induce water stability in the as-electrospun matrix, as demonstrated by infra-red spectroscopy. This reduced complexity in the process since it was not necessary to concentrate silk prior to electrospinning while avoiding the use of toxic solvents to perform a post-processing stabilization treatment which usually causes dimensional changes to the SF materials. Sonication pre-treatment allowed for minimizing the amount of synthetic polymer used to achieve the desirable mechanical properties (with the modulus ranging between 90 and 170 MPa), while avoiding a further water stabilization treatment. It also had a positive impact in the in vitro cell behavior of human primary periodontal ligament cells (hPDLs), resulting in a marked increase in cell proliferation. The present developed work constitutes a step forward towards simplicity and a better fabrication control of viable electrospun SF-based membranes for periodontal regeneration.